2020
DOI: 10.1111/adb.12885
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorder and cannabis use disorder symptomatology in adolescents is associated with dysfunction in neural processing of future events

Abstract: Two of the most commonly used substances by adolescents in the United States are cannabis and alcohol. Cannabis use disorder (CUD) and alcohol use disorder (AUD) are associated with impairments in decision-making processes. One mechanism for impaired decision-making in these individuals is thought to be an inability to adequately represent future events during decision-making. In the current study involving 112 adolescents, we used a comparative optimism task to examine the relationship between relative severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Adolescents often engage in co-morbid alcohol/cannabis use ( Duncan et al, 2015 ; Moss et al, 2014 ). While the majority of the literature to date examines AUD and CUD individually ( Beck et al, 2009 ; Jager et al, 2013 ; Martz et al, 2016 ; Nees et al, 2015 ), emerging data indicates that there are differences in individual associations of AUD and CUD symptomatology levels to neuro-cognitive alterations ( Aloi et al, 2021 , 2020 , 2019 , 2018 ; Blair et al, 2019 ; Leiker et al, 2019 ). More specifically, prior work has shown that AUD symptomatology level is negatively associated with recruitment of regions implicated in top-down attentional and reward processes ( Aloi et al, 2020 , 2019 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents often engage in co-morbid alcohol/cannabis use ( Duncan et al, 2015 ; Moss et al, 2014 ). While the majority of the literature to date examines AUD and CUD individually ( Beck et al, 2009 ; Jager et al, 2013 ; Martz et al, 2016 ; Nees et al, 2015 ), emerging data indicates that there are differences in individual associations of AUD and CUD symptomatology levels to neuro-cognitive alterations ( Aloi et al, 2021 , 2020 , 2019 , 2018 ; Blair et al, 2019 ; Leiker et al, 2019 ). More specifically, prior work has shown that AUD symptomatology level is negatively associated with recruitment of regions implicated in top-down attentional and reward processes ( Aloi et al, 2020 , 2019 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, prior work has shown that AUD symptomatology level is negatively associated with recruitment of regions implicated in top-down attentional and reward processes ( Aloi et al, 2020 , 2019 , 2018 ). CUD symptomatology level is negatively associated with recruitment of regions implicated in emotional responding ( Aloi et al, 2021 ; Blair et al, 2019 ; Leiker et al, 2019 ). Recent neuropsychological data has suggested that alcohol use is associated with poorer performance on visuospatial tasks while greater cannabis use is associated with poorer performance on inhibitory control and visuospatial tasks ( Infante et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has revealed reduced responsiveness in cortical regions involved in emotion processing, such as areas of the PFC, cingulate cortex, and visual areas in individuals with CUD (Aloi et al, 2021; Blair et al, 2019; Leiker et al, 2019). We hypothesized that individuals with CUD would show reduced amygdala connectivity with at least some of these regions.…”
Section: Discussionmentioning
confidence: 99%
“…There are also data to suggest that there may be neural dysfunctions specific to CUD, particularly with regard to emotion processing. For example, a study of adolescents showed that CUD symptom severity was inversely associated with activity within the subgenual anterior cingulate cortex (ACC) and posterior cingulate cortex (PCC) when participants imagined themselves in emotionally salient future situations (Aloi et al, 2021). Importantly, alcohol use disorder (AUD) symptom severity was not associated with these effects (Aloi et al, 2021), and the same was true in other related studies (Aloi et al, 2021; Blair et al, 2019; Leiker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…None of these participants have been included in previous papers on this task. However, a number of the participants have been involved in previously published studies associating specific forms of neuro-cognitive dysfunction with severity of AUD/CUD (25,(48)(49)(50)(51)(52). Six youths were excluded due to incomplete data.…”
Section: Participantsmentioning
confidence: 99%